PENERAPAN TEKNIK CINEMA THERAPY DALAM LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Musdalifah; Sinring, Abdullah; Fitriana (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study focuses on testing the effect of the application of cinema therapy techniques in group guidance services in increasing the learning motivation of students at SMP Negeri 26 Makassar. The objectives of the study include: (1) an overview of the level of student learning motivation, (2) an overview of the implementation of cinema therapy techniques in group guidance services, (3) the effect of the application of cinema therapy techniques in increasing learning motivation. This research approach is quantitative with a quasi-experimental design through a pretest-posttest control group design. The instrument used is a learning motivation scale. The study population was 50 students identified as having low learning motivation. The study sample was 20 grade VIII students who were divided into two groups, namely the experimental group and the control group, each consisting of 10 students. The sampling technique used proportional random sampling. Data collection techniques used were observation and a learning motivation scale. Data were analyzed using descriptive statistics, inferential statistics, and t-tests. The results of the study showed that before the intervention, students' learning motivation was in the low to moderate category. After the intervention, the learning motivation of the experimental group increased to the high category, while the control group remained in the low category. The cinema therapy technique was implemented systematically over six sessions over a five-week period, through the stages of disassociation, identification, internalization, and transference. The t-test results showed a sig. (2-tailed) value of 0.002 < 0.05, so it can be concluded that the cinema therapy technique is effective in increasing students' learning motivation.